2017
DOI: 10.1186/s12885-017-3700-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral primary care: an analysis of its impact on the incidence and mortality rates of oral cancer

Abstract: BackgroundOral cancer is a potentially fatal disease, especially when diagnosed in advanced stages. In Brazil, the primary health care (PHC) system is responsible for promoting oral health in order to prevent oral diseases. However, there is insufficient evidence to assess whether actions of the PHC system have some effect on the morbidity and mortality from oral cancer. The purpose of this study was to analyze the effect of PHC structure and work processes on the incidence and mortality rates of oral cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 64 publications
1
46
0
7
Order By: Relevance
“…Though there is a huge role of preventive initiatives on control of oral cancer incidence and mortality; yet there is a very limited study that addresses the role of primary health care on the female population to reduce the rate of oral cancer incidence and mortality. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though there is a huge role of preventive initiatives on control of oral cancer incidence and mortality; yet there is a very limited study that addresses the role of primary health care on the female population to reduce the rate of oral cancer incidence and mortality. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…With minimal equipment, primary health care providers can easily identify risk factors and perform an early diagnosis to provide basic care for oral cancer and precancer patients. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this investigation demonstrated that the population size of the cities, the socioeconomic status of the population and the availability of public dental services in uence the risk of hospitalization due to oral cancer in Brazil. Two previous studies have developed similar analyses of oral cancer rates, involving socioeconomic characteristics and dental coverage in the SUS among the regions and states of Brazil 13,15 . However, the present study considered for analysis a more comprehensive period and all cities in the country as sample units.…”
Section: Discussionmentioning
confidence: 99%
“…With the progress of surgical, chemotherapeutic and radiotherapeutic techniques, the life qualities of TSCC patients had improved a lot compared to the situation of 10 years before. However, the 5‐year survival rates of TSCC patients remained less than 50% 4,5 . Hence, it is urgent to find out novel therapeutic target and prognostic biomarkers for TSCC.…”
Section: Introductionmentioning
confidence: 99%